Nuclear receptor NR5A2 controls neural stem cell fate decisions during development - Athanasios Stergiopoulos (Nature Portfolio, 2016)
The molecular signals regulating the decision of neural stem cells (NSC) to proliferate versus differentiate are unclear. Here, the authors identify the nuclear receptor NR5A2 as coordinating cell-cycle exit with differentiation of NSCs via direct actions on Ink4, Prox1, Notch1 and JAK/STAT.